Automatic Perfume-Ingredients Mixer for Making One Type of Perfume using a Microcontroller - Ibrahim Ashari; Anis Artiyani (Merdeka Malang University, 2022)
Parfume is a tool that we often use in our daily life. The fragrance of the perfume we use is also diverse to prevent user boredom. In addition, the smell of perfume is also a match for the consumer itself. The rapid development of technology lately indirectly affects the changes in the broader community. The many sophisticated inventions evidence the development of this technology.Along with developing this technology, the equipment can be created to facilitate and provide production speed. In other words, it can increase the quality and quantity of producing goods for the users of these tools. With these technological advances, it can be used to make perfume-ingredients mixing tools to manufacture one type of perfume using a microcontroller. The test results of this tool after manual settings are obtained automatically on measuring cup 1 containing 19cc, cup 2 containing 10cc, cup 3 containing 19cc, cup 4 containing 18cc, and cup 5 containing 29cc. With an average error rate from testing the entire system of 4,8%, the system is declared to be able to work well